Pre-pregnancy BMI, gestational weight gain and postpartum weight retention: a meta-analysis of observational studies. Issue 12 (20th November 2014) - Rong, Ke; Yu, Kai; Han, Xiaolong; Szeto, Ignatius MY; Qin, Xueying; Wang, Junkuan; Ning, Yibing; Wang, Peiyu; Ma, Defu
Abstract: Objective: To determine the association of gestational weight gain (GWG) or pre-pregnancy BMI with postpartum weight retention (PPWR). Design: Meta-analysis. Setting: PubMed, Cochrane Controlled Trials Register, EMBASE, Science Citation Index Expanded, Current Contents Connects and Biosis Previews were used to search articles. Subjects: Publications that described the influence of pre-pregnancy BMI or GWG on PPWR. Results: Seventeen studies that satisfied the eligibility criteria were included in the analyses. Women with inadequate and excessive GWG had significantly lower mean PPWR of −2·14 kg (95 % CI –2·43, –1·85 kg) and higher PPWR of 3·21 kg (95 % CI 2·79, 3·62 kg), respectively, than women with adequate GWG. When postpartum time spans were stratified into 1–3 months, 3–6 months, 6–12 months, 12–36 months and ≥15 years, the association between inadequate GWG and PPWR faded over time and became insignificant (−1·42 kg; 95 % CI −3·08, 0·24 kg) after ≥15 years. However, PPWR in women with excess GWG exhibited a U-shaped trend; that is, a decline during the early postpartum time span (year 1) and then an increase in the following period. Meta-analysis of qualitative studies showed a significant relationship between excessive GWG and higher PPWR risk (OR=2·08; 95 % CI 1·60, 2·70). Moreover, meta-analysis of pre-pregnancy BMI on PPWR indicated that mean PPWR decreased with increasing BMI group. Conclusions: These findings suggest that GWG, rather than pre-pregnancy BMI, determines the shorter- or longer-term PPWR.